اتجاهات الطلبة الناطقين بغير العربية في ماليزيا نحو استخدام برنامج تعليمي قائم على التعلّم التشاركي عبر شبكة التواصل الاجتماعي / The Attitudes among Non-Arabic Speaking Students in Malaysia towards Using an Educational Programme Based on Collaborative Lea - Bin Abdul Hamid, Mohamed Azrol Azlan; Moqbil Al Khawaldah, Ahmed Hamad (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2017)
ملخص البحث: تهدف هذه الدراسة إلى التعرف على اتجاهات طلبة الجامعة في ماليزيا نحو استخدام برنامج تعليمي قائم على التعلم التشاركي عبر شبكة التواصل الاجتماعي في تحسين مهارة الكتابة باللغة العربية، وتتكون عينة الدراسة من (25) طالباً وطالبةً في الجامعة الإسلامية العالمية بماليزيا للعام الدراسي 2014/2015م، وتم اختيارهم بالطريقة القصدية، ولتحقيق هدف الدراسة قام الباحث ببناء أداة الدراسة المتمثلة بالاستبانة. أشارت نتائج الدراسة إلى قوة اتجاهات الطلبة نحو البرنامج المقترح في تحسين مهارة الكتابة، وكانت الاتجاهات قوية في النواحي الآتية: أولاً، تصميم البرنامج التعليمي بمتوسط حسابي 4.02 وانحراف معياري 0.701، وثانيًا، التغذية الراجعة بمتوسط حسابي 3.86 وانحراف معياري 0.726، وثالثًا، الفيسبوك كأداة التعلم التشاركي بمتوسط حسابي 3.83 وانحراف معياري 0.750، ورابعًا، استخدام الكتابة التشاركية في تعلم اللغة بمتوسط حسابي 3.67 وانحراف معياري 0.624، وأخيرًا أثر البرنامج التعليمي بمتوسط حسابي 3.63 وانحراف معياري 0.727، وإجمالاً فإن الاتجاهات في الدرجة الكلية كانت قوية، حيث كانت بمتوسط حسابي 3.80 وانحراف معياري 0.706، وفي ضوء النتائج التي توصلت إليها هذه الدراسة فإن الباحث يوصي بضرورة تفعيل التعلم التشاركي من خلال شبكة التواصل الاجتماعي في تعليم مهارة الكتابة باللغة العربية. الكلمات المفتاحية: التعلم التشاركي- شبكة التواصل الاجتماعي- مهارة الكتابة- تعليم اللغة، غبر الناطقين. Abstract: This study aimed at identifying the perceptions among university students in Malaysia towards using an educational programme based on collaborative learning via social networking in improving Arabic language writing. The participants of the study were selected purposely who consisted of 25 International Islamic University Malaysia students in the academic year 2014/2015. To fulfill the aim of the study, the researcher developed questionnaires to gather data. The results had shown that the perceptions of students towards the use of the proposed educational programme in improving writing skill was strong. The mean for designing the educational programme was 4.02 with the standard deviation of 0.701. The mean for feedback was 3.86 with the standard deviation of 0.726. Facebook as a collaborative tool scored high with the mean, 3.83 and the standard deviation, 0.750. The use of collaborative writing in Arabic language learning also scored high with the mean of 3.67 and the standard deviation of 0.624. While the mean for effect of the educational programme was 3.63 with the standard deviation of 0.727. The overall scores were high with the mean of 3.80 and the standard deviation of 0.706. In view of the study results, the researcher recommends the necessity of activating the collaborative learning via social networking in the teaching of Arabic writing skill. Keywords: Collaborative learning, Social networking, Writing skill, Teaching Arabic language, non-native speakers. Abstrak: Kajian ini bertujuan untuk mengenal pasti persepsi pelajar universiti di Malaysia terhadap penggunaan program pendidikan berasaskan pembelajaran kolaboratif melalui laman jaringan sosial untuk memperbaiki kemahiran menulis. Peserta kajian ini terdiri daripada 25 orang pelajar Universiti Islam Antarabangsa Malaysia. Dapatan kajian menunjukkan tahap persepsi pelajar terhadap penggunaan program pendidikan yang dicadangkan bagi memperbaiki kemahiran menulis adalah tinggi. Min bagi rekabentuk program pendidikan adalah 4.02 dengan sisihan piawai 0.701. Min bagi maklumbalas pula adalah 3.86 dengan sisihan piawai 0.750. Manakala min bagi Facebook sebagai alat kolaborasi pula mencatatkan min 3.83 dengan sisihan piawai 0.750. Penggunaan penulisan secara kolaborasi dalam pembelajaraan bahasa Arab juga mencatatkan pencapaian yang tinggi iaitu dengan min 3.67 dan sisihan piawai 0.624. Kesan program pendidikan pula memperoleh min 3.63 dengan sisihan piawai 0.727. Pencapaian secara keseluruhannya adalah tinggi dengan min 3.80 dan sisihan piawai 0.706. Berdasarkan keputusan ini, pengkaji mencadangkan penggunaan pembelajaran secara kolaborasi melalui laman jaringan sosial dan pengajaran kemahiran menulis di dalam bahasa Arab. Kata kunci: Pembelajaran kolaboratif, Jaringan sosial, Kemahiran menulis, Pengajaran bahasa Arab, penutur bukan Arab.